HUBUNGAN KEPEMILIKAN BUKU KIA DENGANPENGETAHUAN DAN SIKAP IBU HAMIL TENTANG PERAWATAN KEHAMILAN DI PUSKESMAS FATUKANUTU KABUPATEN KUPANG TAHUN 2013 - HANIFAH, ASTIN NUR (Jurnal Kebidanan: MIDWIFERY MEDICAL JOURNAL, 2014)
Background: Mothernal and Child Book (MCB) is a tool to monitoring health status of mother and child. The aim of MCB are to incerase community knowledge of maternal health especially pregnancy women, so they can have a health and clean living behaviour and can prevent the risky pregnancy, anemia of preganant women, IUGR,maternal and child death, lack nutrition of todler and preganant women. In Fatukanutu community health center have pregnancy women targeted 209 in 2012, acses to health center in July to December in 2012 is 44 %, who gave MCB : 84 Pregnant women (40 %), high risk pregnant women : 26 case (12,4%), reference to hospital : 12 case (5,7 %).Objective: Knowing correlation between MCB with knowledge and attitude of pregnant women about Pregnancy care.Method: This research using cross sectional design, with total sampling and sampling tecnik is non random sampling, 92 pregnancy women, instrument using in this research in kuesionet with close ended question.Result: Lot of pregnancy women have a good knowledge about pregnancy care is 33 case (47,1% ), all pregnant women have positife attitude is 40 respondent (57,1%). So there is have a significant correlation between having MCB with their knowledge and attitude about pregnancy care.